Literature Review: Effectiveness of P6 Acupressure in Reducing First-Trimester Pregnancy Nausea and Vomiting - Janah, Sipatul; Pujianti, Neli; Rahma Idhiana, Nindya; Rizkiyah; Carolina, Evita; Windayanti, Hapsari (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Emesis gravidarum is a common condition experienced by women during the first trimester of pregnancy, characterized by nausea and vomiting due to hormonal changes, particularly increased levels of human chorionic gonadotropin and estrogen. If not properly managed, this condition may progress to hyperemesis gravidarum, which can lead to dehydration, electrolyte imbalance, weight loss, and negatively affect maternal quality of life. Therefore, appropriate and safe management strategies are essential to prevent further complications. One widely used non-pharmacological therapy is acupressure at the Pericardium 6 (P6) point, which is considered safe, simple, cost-effective, and associated with minimal side effects. This study aimed to analyze the effectiveness of P6 acupressure in reducing nausea and vomiting among first-trimester pregnant women based on published research findings. This study employed a literature review using a narrative approach. Data were obtained from national and international journals through electronic databases, including Google Scholar and PubMed, published between 2021 and 2026. Articles were selected based on predefined inclusion and exclusion criteria, such as relevance to the research topic, availability of full text, and measurable outcomes. The selected studies were analyzed using content analysis techniques, focusing on research design, sample characteristics, intervention procedures, outcome measures, and key findings. A total of eight relevant studies were included and systematically compared based on research design, sample size, statistical results, and clinical implications. The findings indicate that most studies demonstrate that P6 acupressure is effective in reducing the frequency and intensity of nausea and vomiting. Several studies reported statistically significant results (p < 0.05), while one randomized controlled trial showed non-significant results despite observable clinical improvement. In addition, acupressure was found to reduce the use of antiemetic medications and improve maternal comfort and quality of life. Overall, the evidence suggests that P6 acupressure has consistent therapeutic potential as a complementary intervention. Therefore, P6 acupressure can be recommended as a safe and effective non-pharmacological therapy in managing emesis gravidarum, although further high-quality studies are needed to strengthen the evidence.